2021
DOI: 10.1371/journal.pone.0259589
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at first alcohol use and heavy episodic drinking: An analysis of Thailand’s smoking and alcohol drinking behavior survey 2017

Abstract: According to evidence from developed countries, age at first alcohol use has been identified as a determinant of heavy episodic drinking (HED). This study aimed to investigate the association between age at first alcohol use and HED using data from the Smoking and Drinking Behavior Survey 2017, a Thai nationally representative survey. Binary logistic regression was used to examine the association. This study used data from 23,073 current drinkers in the survey. The survey participants were chosen to represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…In Thailand, many researchers have studied alcohol consumption, but few have focused on the role of peers in alcohol consumption. Instead, they have tended to study the phenomenon from other standpoints such as analyzing alcohol consumption trends in the country [22][23][24][25]. In 2001, European Addiction Research data showed that Thais consumed an average of 2 liters of unmixed alcohol per capita in 1995.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Thailand, many researchers have studied alcohol consumption, but few have focused on the role of peers in alcohol consumption. Instead, they have tended to study the phenomenon from other standpoints such as analyzing alcohol consumption trends in the country [22][23][24][25]. In 2001, European Addiction Research data showed that Thais consumed an average of 2 liters of unmixed alcohol per capita in 1995.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Časný začátek užívání alkoholu je spojen s těžkým epizodickým pitím i u žen. Pravidelné pití alkoholu, pití doma a vystavení reklamě na alkohol zvyšuje pravděpodobnost výskytu tohoto jevu (Sonthon et al 2021). Zkušenost s alkoholem má přes 40 % dětí ve věku 13 let, 25 % dětí ve věku 15 let uvádí alespoň dvakrát výskyt opilosti.…”
Section: Abúzus Návykových Látek V Evropě a čEské Republiceunclassified
“…Between 2011 and 2014, the state of Georgia (southeastern region) had bingeing rates between 13.1 % and 16.6 %. Traditional studies of bingeing focus on age at rst use and its contribution to subsequent heavy drinking [23,24]. While the prevalence of bingeing is well-documented, less is known about the individual, social, and contextual factors that initiate bingeing [25,26].…”
Section: Introductionmentioning
confidence: 99%